1995
DOI: 10.1016/s1078-5884(05)80194-7
|View full text |Cite
|
Sign up to set email alerts
|

Carotid artery plaque composition — Relationship to clinical presentation and ultrasound B-mode imaging

Abstract: Objective: To correlate B-mode ultrasound findings to carotid plaque histology. Design: European multicentre study (nine centres). Material and Methods: Clinical presentation and risk factors were recorded and preoperative ultrasound Duplex scanning with special emphasis on B-mode imaging studies was performed in 270 patients undergoing carotid endarterectomy. Perioperatively, macroscopic plaque features were evaluated and the removed specimens were analysed histologically for fibrous tissue, calcification and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
3
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(4 citation statements)
references
References 32 publications
0
3
1
Order By: Relevance
“…Although other studies showed significant correlation between high echogenicity and calcified plaques [ 39 , 40 ], our study did not confirm this association. Our results indicate that the echogenic plaques are predominantly calcified and also some of the echolucent, vulnerable plaques show a variable degree of calcification.…”
Section: ⧉ Discussioncontrasting
confidence: 99%
“…Although other studies showed significant correlation between high echogenicity and calcified plaques [ 39 , 40 ], our study did not confirm this association. Our results indicate that the echogenic plaques are predominantly calcified and also some of the echolucent, vulnerable plaques show a variable degree of calcification.…”
Section: ⧉ Discussioncontrasting
confidence: 99%
“…The risk of stroke was predicted estimating the diameter reduction of internal carotid artery (ICA) and evaluating plaque morphology (25). Patients with symptoms of stroke, transient ischemic attack (TIA) or amaurosis fugax within 6 months since diagnosis of carotid artery disease were defined symptomatic (2628).…”
Section: Methodsmentioning
confidence: 99%
“…We additionally reclassified individuals into 4 clinical categories that have been shown to be useful in terms of future outcomes [16]: Echolucent (lipid- and haemorrhage-rich plaques), mixed (when patients had both echolucent and echo-rich plaques), echogenic (fibrotic or fibro-fatty plaque); and extensively calcified plaques (echo-shadowing from calcifications) as previously described [9]. This classification has been validated against histopathology [9,22] and grey scale medium measured on ultrasound images [23]. The arterial territories explored included the common and internal carotid territories and the bifurcation from the left and right carotid arteries.…”
Section: Methodsmentioning
confidence: 99%